The scholars of the city of Azerbaigan in the era of the ilKhanids (651-756H\1253-1355M) - Sadiq Abdul-Amir , Jaffer (Journal of College of Education, 2021)
Scientific life flourished in a number of Azerbaijani cities during the era of the Mongol ilKanis, and this is due to the interest of the Mongol ilKhans in science and scholars, and this was illustrated by the emergence of a number of scholars who specialized in several scinentific fields, and they classified a number of works in most sciences, a number of which are still preserved in some of the worlds libraries-these scholars have paid attention to the scientific journey through their travel to several countries in order to seek knowledge and to hold their seminars and scientific councils in them, and a large number of them have assumed important positions in the state for their sincerity, scientific intejrity and their administrative and political experience.
Keywords: Elkhanyans , Historical Compilations , scientific life